2020
DOI: 10.1088/1674-1056/ab6717
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of femtosecond surface plasmon polariton*

Abstract: As the combination of surface plasmon polariton and femtosecond laser pulse, femtosecond surface plasmon polariton has both nanoscale spatial resolution and femtosecond temporal resolution, and thus provides promising methods for light field manipulation and light–matter interaction in extreme small spatiotemporal scales. Nowadays, the research on femtosecond surface plasmon polariton is mainly concentrated on two aspects: one is investigation and characterization of excitation, propagation, and dispersion pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 101 publications
1
14
0
Order By: Relevance
“…Modern pharmacological studies have found that gypsum has a strong and rapid antipyretic effect, and it is also effective in regulating the metabolic disorders of trace elements caused by pathological changes and enhancing the bactericidal immunity of the body [12]. Yang Liu et al found that gypsum can achieve antipyretic and anti-inflammatory effects by regulating PGE2 content [13]. The above three kinds of traditional Chinese medicine are combined in reasonable doses to promote blood circulation and remove blood stasis, reduce swelling and relieve pain, and have the effects of anti-inflammatory and sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological studies have found that gypsum has a strong and rapid antipyretic effect, and it is also effective in regulating the metabolic disorders of trace elements caused by pathological changes and enhancing the bactericidal immunity of the body [12]. Yang Liu et al found that gypsum can achieve antipyretic and anti-inflammatory effects by regulating PGE2 content [13]. The above three kinds of traditional Chinese medicine are combined in reasonable doses to promote blood circulation and remove blood stasis, reduce swelling and relieve pain, and have the effects of anti-inflammatory and sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…A new underlying physical mechanism of nonlinear trapping has recently been reported [346][347][348][349][350][351] , which offers an alternative approach for exploring the physical mechanisms of light-matter interactions 28 . When a femtosecond optical pulse is incident on a metal surface, it might disturb the equilibrium in the energy-momentum distribution of electrons and thereby influence plasmonic excitation and propagation along the surface [352][353][354] . Furthermore, harmonic spin-orbit angular momentum coupling and its a b Fig.…”
Section: Nonlinear Plasmon-matter Interactionsmentioning
confidence: 99%
“…where k SPP (ω) =2π/λ SPP (ω) denotes the wave vector of SPP, with λ SPP (ω) the wavelength of the SPP 12 ,…”
Section: / 14mentioning
confidence: 99%
“…To demonstrate this 2-D spatiotemporal FT method for on-chip devices, we chose surface plasmon polaritons (SPP) excited on a metal surface as carriers of on-chip optical signals, and studied modulation effects of femtosecond SPP pulses. With their capability of breaking through the optical diffraction limit 12 , SPPs are widely employed in nanophotonic devices used in a variety of applications including optical storage 13 , optical sensing 14 , optical tweezers 15 , and Raman scattering 16 . In addition to nanoscale spatial resolutions, SPP pulses generated by a femtosecond laser beam enable femtosecond-scale temporal resolutions, thereby providing a research platform to investigate the manipulation of light fields and the interaction of light and matter at extremely small spatiotemporal scales.…”
Section: / 14mentioning
confidence: 99%
See 1 more Smart Citation